Public Service Information System at the Department of Public Works Development and Spatial Planning - Naipospos, Bintang; Evi (Journal of Computer Science Application and Engineering (JOSAPEN), 2023)
The Public Service Information System at the Department of Public Works Development and Spatial Planning in South Sumatra Province is a pivotal solution for managing road infrastructure. Roads are crucial for regional development and economic progress. This system, utilizing the prototype model, Object-Oriented Analysis and Design (OOAD), and Unified Modeling Language (UML) tools, facilitates effective monitoring, reporting, and resolution of road damage. The methodology involves iterative prototyping, ensuring a clearer understanding of requirements and reducing risks. The system design includes various UML diagrams, depicting system functionalities, actors, and interactions, while its architecture outlines a streamlined flow of information. Initial testing validated the system's effectiveness, showcasing its ability to handle functions and interfaces proficiently. Overall, this system significantly contributes to efficient road infrastructure management, meeting community needs, and government responsibilities for effective public services. Acknowledgments are extended to the South Sumatra Public Works Department of Highways and Spatial Planning for their support.